Predicting postural control adaptation measuring EEG, EMG, and center of pressure changes: BioVRSea paradigm - Stehle, Simon A.; Aubonnet, Romain; Hassan, Mahmoud; Recenti, Marco; Jacob, Deborah; Petersen, Hannes; Gargiulo, Paolo (Frontiers in Human Neuroscience, 2022)
Postural control is a sensorimotor mechanism that can reveal neurophysiological disorder. The present work studies the quantitative response to a complex postural control task. We measure electroencephalography (EEG), electromyography (EMG), and center of pressure (CoP) signals during a virtual reality (VR) experience called BioVRSea with the aim of classifying different postural control responses. The BioVRSea paradigm is based on 6 different phases where motion and visual stimulation are modulated throughout the experiment, inducing subjects to a different adaptive postural control strategy. The goal of the study is to assess the predictability of those responses. During the experiment, brain activity was recorded from a 64-channel EEG, muscle activity was determined with 6 wireless EMG sensors placed on lower leg muscles, and the individual movement measured by the CoP. 172 healthy individuals underwent the BioVRSea paradigm and 318 features were extracted from each phase of the experiment. Machine learning techniques were employed to 1. Classify the phases of the experiment 2. Assess the most notable features 3. Identify a quantitative pattern for healthy responses. The results show that the EEG features are not sufficient to predict the distinct phases of the experiment, but they can distinguish visual and motion onset stimulation. EMG features and CoP features, when used jointly, can predict 5 out of 6 phases with a mean accuracy of 74.4% (± 8%) and an AUC of 0.92. The most important feature to identify the different adaptive strategy is the Squared Root Mean Distance of points on Medio-Lateral axis (RDIST_ML). This work shows the importance and the feasibility of a quantitative evaluation in a complex postural control task and demonstrates the potential of EEG, CoP, and EMG for assessing pathological conditions. These predictive systems pave the way for developing objective assessment of pathological behavior PC responses. This will be a first step in identifying individual disorders and treatment options.